Psychological compliance techniques for marketing sports product / Vincent Parnabas ... [et al.] - Parnabas, Vincent; Parnabas, Julinamary; Parnabas, Antoinette Mary; Mahamood, Yahaya; Fauzee, Mohd Sofian Omar; Haji Mohd Nor, Mohad Anizu (Universiti Teknologi MARA, Shah Alam: Malaysian Academy of SME and Entrepreneurship Development (MASMED), 2018)
The main purpose of this study is to identify the effectiveness of psychological compliance techniques approach to promote sports product to the customers. Therefore, this survey aims to determine the most preferred psychological techniques of promoting sports product. The instrument used for this study is a 20-item Psychological Compliance Techniques questionnaire which had been distributed to sports product managers. The questionnaire included 4 techniques of promoting such as Foot-In-The-Door, Lowball Technique, Door-In- Face-Technique and That's-Not-All-Technique. The respondents consist of 75 managers, including, top-level managers (N=12), middle-level managers (N=25) and low-level managers (N= 38). The results show that the most effective psychological compliance techniques for marketing sports product for top-level managers are That's-Not-All-Technique, F (2, 75) = 13.625, p < .01, and Lowball technique, F (2, 75) = 11.418, p < .01. While, Door-In-Face technique, F (2, 75) = 15.559, p < .01., and Foot-In-The-Door technique, F (2, 75) = 12.314, p < .01., are the most effective Psychological Compliance Techniques for Marketing Sports Product for low-level managers. Sports industry can use this psychological compliance techniques to market their sports product effectively and efficiently. Psychological compliance techniques are useful methods in changing customers' behaviour due to the request or direction of sales personnel.